Empowering communications challenged users using development kits - Dissanayake, W.; Prasad, C.; Singh, Ashutosh Kumar (WORLD ACADEMY OF SCIENCE, ENGINEERING AND TECHNOLOGY, 2012)
The rapid pace of technological advancement and its consequential widening digital divide has resulted in the marginalization of the disabled especially the communication challenged. The dearth of suitable technologies for the development of assistive technologies has served to further marginalize the communications challenged user population and widen this chasm even further. Given the varying levels of disability there and its associated requirement for customized solution based. This paper explains the use of a Software Development Kits (SDK) for the bridging of this communications divide through the use of industry poplar communications SDKs towards identification of requirements for communications challenged users as well as identification of appropriate frameworks for future development initiatives.